Uptake, translocation and metabolism of decabromodiphenyl ether (BDE-209) in seven aquatic plants. (June 2016) - Deng, Daiyong; Liu, Jin; Xu, Meiying; Zheng, Guolu; Guo, Jun; Sun, Guoping
Abstract: Terrestrial plant uptake of PBDEs from contaminated soils has been widely reported recently. In this study the fate of deca-BDE within a plant/PBDEs/aquatic environment system was investigated through simulated pot experiments. Accumulations of the total PBDEs and deca-BDE were observed in tissues of seven test aquatic plant species, namely Phragmites australis, Cyperus papyrus, Alternanthera philoxeroides, Colocasia esculenta, Scirpus validus, Acorus calamus and Oryza sativa . In all seven plants, O. sativa leads the uptake and accumulation both in the total PBDEs (444.8 ng g −1 ) and deca-BDE (368.0 ng g −1 ) in roots. Among the six common phytoremediation aquatic plants, A. calamus leads the uptake (236.2 ng g −1 ), and P. australis leads the translocation ( C shoot / C root = 0.35), while A. philoxeroides (43.4%) and P. australis (80.0%) lead in the metabolism efficiencies in the root and shoot, respectively. The detection of seventeen lesser brominated PBDE congeners provided the debromination evidence, and the specific PBDEs profiles in test plant species indicated there is no common metabolic pattern. Furthermore, a relative high proportion of lesser brominated PBDE congeners in shoots suggested the possible metabolic difference between roots and shoots. Finally, a noticeable percentage of penta- and octa-BDE derived from deca-BDE also hint the ecological risk in deca-BDE use. This comparative research on the aquatic plants provide a broad vision on the understanding of plant/PBDEs/aquatic environment interaction system, and may be applied to remediate PBDEs in contaminated waters and sediments. Graphical abstract: Highlights: All the seven test aquatic plants displayed removal capabilities for deca-BDE. Significant differences for deca-BDE uptake efficacy observed. Notable variation of Cshoot /Croot and specific PBDE congener profiles observed. Noticeable percentage of penta- and octa-BDE derived from deca-BDE detected. Phytoremediation of deca-BDE is potential but the plant selection is considerable.